(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2025)
This study examines the syntactic realization of diminutives in English, Spanish, and Uzbek. It demonstrates that English relies on adjective–noun constructions (“little + N”), Spanish utilizes productive diminutive suffixes ( ito/a, -illo/a), and Uzbek employs agglutinative suffixation (-cha, -jon, -gina) alongside syntactic modifiers. The findings highlight that diminutives function as both grammatical and pragmatic devices, reflecting the typological properties of each language.